Binarizacija vanjske politike / Binarization of Foreign Policy Conduct: Tko je izgubio nesvrstane? / Who Lost NAM? - H. Bajrektarević, Anis (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The text has so far been published in over twenty countries on four continental worlds. From the English original: Binarization of Foreign Policy Conduct - Who lost US? Translated by M. Sci. Iva Kožul (revised by Author).